ANALISIS NORMATIF PENGATURAN PRINSIP-PRINSIP DEMOKRASI DALAM LEGISLASI PERATURAN DAERAH - Anis Ibrahim (Widya Yuridika, 2019)
"> Since regional autonomy is broadly implemented, the existence of Perda (local regulation) isone of the central issues and becomes unending controversies, marked by many unaspirativePerda. “Certainly, the existence of the Perda are not separated from the rules that as the basefor the legislational process of the Perda. After being analyzed based on principles ofdemocracy, it can be concluded that various regulations on from which to base the formationof Perda, some have been based on the prniciples, some have not. Those that have been basedon the principles should be perfected in detail so that the legislational process of the perdaworks in the proper track of substantial democracy.